Peningkatan Kualitas Layanan Konten Jurnal Melalui Rebranding (Studi Kasus di Perpustakaan Universitas Andalas) - Shinta Tri Septiani; Elva Rahmah (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research is to describe and analyze the effectiveness and service strategies in the Library of UNAND, requiring techniques that are expected to improve the quality of service is through rebranding. Data collection tool that is used to describe the qualitative data are observation, field notes, interviews with library staff, and literature. Analyzing the data be descriptive. By analyzing the data, it was concluded the following. First, the implementation of the rebranding at the Library of UNAND not vitiated financial, library management, to own inviters. Second, service strategies through rebranding less applied in Library of UNAND.